FUNCTIONALISATION OF ETHYLENE-PROPYLENE COPOLYMER (EPM) BY MELT GRAFTING OF MALEIC ANHYDRIDE (MAH) USING HIGH SHEAR INTERNAL MIXER - Mohamad, Noraiham; Mahamood, Mazlin Aida; Yaakub, Juliana; Abdul Razak, Jeefferie; Muchtar, Andanastuti; Shueb, Mohammed Iqbal; Kasim, Mohd Shahir; Mohd Abid, Mohd Asyadi Azam; Yaakob, Mohd Yuhazri; Mustafa, Nuzaimah; Toibah, Abd Rahim; Qumrul, Ahsan (2013)
MAH grafted EPM is a highly potential compatibiliser in EPDM based blend. This studyjs focusing on synthesizing peroxide-initiated MAH-g-EPM via melt grafting using a Haake intemal mixer at high shear rate. The effect of MAH and dicumyl (DCP) percentage on the grafting efficiency of MAH onto EPM chains was carried out through a 2-level factorial experimental design using the Design Expert 6.0.5 software. The MAH and DCP content were varied in the range of 1-5 phr and 0.1-0.3 phr, respectively. The grafting parameters were fixed at temperature of 180°C, rotor speed of 60 rpm for 5 minutes. The grafting efficiency was determined by Fourier Transform Infrared spectroscopy analysis based on cumulative absorbance of anhydrides characteristic peaks. It was observed to be highly 'j 'f influenced by the amount of MAH and DCP and the optimum funtionalisation was achieved at 5 phr MAH and 0.3 phr peroxide addition